Pengaruh Tadarus Al-Qur’an terhadap Sikap Menghargai Sesama Manusia: Penelitian Eksperimen pada Kasus Bullying Siswa SD Kelas 2 SDIT Bhakti Pertiwi Baleendah Bandung - Irma Yanti (Jurnal Penelitian Ilmu Ushuluddin, 2022)
Mutual respect for fellow human beings needs to be applied since the child's early life, a design that can be applied is one of them with tadarus al-Quran. This study intends to gain knowledge about the effect of tadarus al-Qur'an on the attitude of respect for fellow human beings. Quantitative approach with one group pretest and one posttest experimental design used in this study. The data analysis process used the IBM SPSS Statistict 25 application. This study resulted in the opinion that the influential Qur'anic tadarus can increase the attitude of respect for fellow human beings in second grade students of SDIT Bhakti Pertiwi Baleendah Bandung with a probability of 0.000 < 0.05. That is, tadarus al-Qur'an can be an alternative way in developing mutual respect for fellow human beings in children. The entire sample in this study experienced an increase in respect for fellow human beings. As evidenced by descriptive statistical data, it is known that the difference in the average value of mutual respect, before and before learning treatment using the Qur'anic tadarus method for ten times of treatment. This study proves that mutual respect for fellow human beings can be improved through the Qur'anic tadarus learning method.